Distinguishing Doctrine and Theological Theory - A Tool for Exploring the Interface between Science and Faith - Toren, Bernard van den (Science & Christian belief, 2016)
This article explores the value of the distinction between doctrine and theological theory for creating space at the interface between the natural sciences and theology. It argues that in a taxonomy of theological statements, doctrines have a different role and greater weight from theological theories. Doctrines express the teachings of the church that guard Christian identity and regulate the Christian life. As such they also make truth claims that can be in tension with scientific theories, for example concerning the origin of the human species. However, these tensions are often experienced more particularly at the level of theological theories, which are developed to gain a deeper understanding of the reality of the Gospel behind these doctrines. Though these theories are important as an expression of our desire to know God, in order to understand the different facets of human experience and for apologetic reasons, they are of secondary importance compared to doctrines and should be held more lightly. Because theological theories are often more deeply shaped by available cultural thought-forms than doctrines, they can be and sometimes should be exchanged for alternatives that make more sense in the light of the totality of our experience, including insights gained from the natural sciences.